(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article provides information on the social and educational activities of Batken State University (BatMU) in the region and its interaction with the local population. It examines the unique features of BatMU, such as enhancing the social significance of higher education, preserving the intellectual potential and ethnocultural identity of the region’s people, and integrating modern technologies to ensure quality education. The study discusses the socio-economic opportunities of the region, the academic potential of educational institutions, and the commitment of teachers and students to serving their homeland. The article highlights the necessity of considering the population’s needs in science, education, and culture. The establishment of Batken Region and the opening of the university marked new milestones in the development of Kyrgyzstan’s southern region. This study explores the socio-economic development of Batken Region, its cooperation with the local population, and the fulfillment of its educational needs. It also discusses the content and implementation methods of these processes.